Experimental Study and Numerical Simulation of Radiated Noise from Unmanned Underwater Vehicle - Zhang Chunyu; Xu Qiang; Yang He; Peng Zilong; Li Jiangqiao; Zhou Jialiang (Polish Maritime Research)
This paper focuses on the research of the radiation noise of underwater unmanned vehicle (UUV), which is one of the most important indicators for evaluating the performance of underwater unmanned equipment. Integrating experimental study and numerical calculations, this paper investigates the underwater radiated noise characteristics and hydrodynamic properties of the propeller of UUV. Firstly, an open-water radiated noise experiment is conducted. To ensure the accuracy of acoustic test, the UUV are held stationary during the experiment. Then, the hydrodynamic performance of a propeller in a steady flow field is calculated using Computational Fluid Dynamics (CFD). Finally, the noise in the unsteady flow field is calculated using the Ffowcs Williams-Hawkings (FW-H) equation. The results show that the propeller, as the main noise source when the UUV is working, exhibits distinct characteristic line spectra in the frequency response curve. By comparing the numerical and experimental results, it was found that the overall trend of the sound pressure level is similar. But the line spectrum characteristics of the numerical results between 100 and 400 Hz are more obvious, mainly because the simulation model is more idealized compared to the experimental tests. The study further examines the hydrodynamic characteristics, propeller noise, and directional characteristics of UUV under different operating conditions.